2020
DOI: 10.1093/tas/txaa045
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lactose and a prototype Lactobacillus acidophilus fermentation product on digestibility, nitrogen balance, and intestinal function of weaned pigs1

Abstract: The objective of this study was to determine the effects of lactose (LA) and a prototype Lactobacillus acidophilus fermentation product (FP) on growth performance, diet digestibility, nitrogen (N) balance, and intestinal function of weaned pigs. Twenty-eight newly weaned pigs [approximately 21 d of age; initial body weight (BW) = 5.20 ± 0.15 kg] were housed in metabolism crates and assigned to one of four treatments (n = seven pigs per treatment) corresponding to a 2 × 2 factorial design: with (LA+; 15% inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Furthermore, dietary L. acidophilus positively influences gut morphology in animals, as demonstrated via morphometric evaluations. Lactobacillus acidophilus supplementation increased mucosal layer height by improving villus height, whereas crypt depth remained unaffected 66,67 . Also, B. subtilis supplementation can increase the ileal villus height and V/C ratio and serve as an antibiotic substitute for the intestinal ecosystem of weaned piglets 68 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, dietary L. acidophilus positively influences gut morphology in animals, as demonstrated via morphometric evaluations. Lactobacillus acidophilus supplementation increased mucosal layer height by improving villus height, whereas crypt depth remained unaffected 66,67 . Also, B. subtilis supplementation can increase the ileal villus height and V/C ratio and serve as an antibiotic substitute for the intestinal ecosystem of weaned piglets 68 .…”
Section: Discussionmentioning
confidence: 99%
“…The growth‐stimulating effect of probiotics treatment on the intestinal mucosa has been well described 48,59,67 . The local IGF system may have a regulatory effect of on intestinal mucosa growth 28,32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paradoxically, the positive role of dietary supplemental lactose in improving weanling pig growth performance and efficiency of wholebody nitrogen (N) retention has received considerable attention. Crystalline lactose and lactose from dried whey powder are well documented to be the essential dietary carbohydrate for improving growth performance and/or efficiency of the whole-body N retention in weanling pigs (Mahan, 1992;Nessmith et al, 1997;Cromwell et al, 2008;Acosta et al, 2020;Zhao et al, 2021). Mahan and Newton (1993) demonstrated that dextrose was effective but cornstarch was ineffective to replace lactose in improving growth performance and efficiency of the whole-body N utilization in weanling pigs, suggesting that lactose is still likely the highly and rapidly digestible carbohydrate in weanling pigs.…”
Section: Introductionmentioning
confidence: 99%